2019
DOI: 10.3390/molecules24203794
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination and Quantification of Triterpene Saponins from Camellia sinensis Seeds Using UPLC-PDA-QTOF-MS/MS

Abstract: Saponins in the Camellia sinensis seeds have a broad spectrum of biological properties and application potentials. However, up to now, no chromatographic methods have been developed to provide full fingerprinting and quality assurance for these saponins. This research aimed to develop a novel method to tentatively identify and quantify saponins in C. sinensis seeds by ultra-high-performance liquid chromatography coupled with photo-diode array detector and quadrupole time-of-flight mass spectrometry (UPLC-PDA-Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Identification of triterpene saponins by UHPLC‐UV‐MS/MS with CID in negative ion mode is a well‐established and widely employed technique 25,26,41 . Once known compounds are identified in the data set, database searches can be used as a guidance to discover the structure of new metabolites with modified core structures from a given class.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of triterpene saponins by UHPLC‐UV‐MS/MS with CID in negative ion mode is a well‐established and widely employed technique 25,26,41 . Once known compounds are identified in the data set, database searches can be used as a guidance to discover the structure of new metabolites with modified core structures from a given class.…”
Section: Resultsmentioning
confidence: 99%
“…In this work we used MZmine 2 , which contains methods for all data processing stages, such as spectral filtering, peak detection, alignment, normalisation and identification 21 . Recent literature reports this tool for the structural determination of compounds from several metabolite classes such as flavonoids, 19,22 alkaloids, 17,23,24 and saponins 25,26 …”
Section: Introductionmentioning
confidence: 99%
“…For example, compound 13 exhibited a [M+H] + peak at m/z 153.0544 and characteristic fragment ions in the MS 2 spectrum at m/z 125.0595 [M+H‐CO] + , 111.0439 [M+H‐CO‐CH 2 ] + , and 93.0338 [M+H‐C 2 H 4 O 2 ] + . According to previous research [35], compound 13 was identified as vanillin, whose fragmentation pattern is shown in Figure 4h. Notably, compounds 1, 12, 17, 23, and 49 were not reported previously in CRP extracts.…”
Section: Resultsmentioning
confidence: 81%
“…Cells were maintained in RPMI-1640 medium (Sigma, St. Louis, MO, USA) containing 10% fetal bovine serum (FBS) at 37 °C with 5% CO 2 . TSE1 was prepared and identified as reported in our previous work [ 74 ].…”
Section: Methodsmentioning
confidence: 99%